On the tribe Sarimini with two new genera from south of China (Hemiptera, Fulgoromorpha, Issidae) - Wang, Menglin; Zhang, Yalin; Bourgoin, Thierry (Zootaxa, 2019)
Two new genera of the tribe Sarimini are described from south of China. They are Sarimissus gen. nov. with a new species S. maculifrons sp. nov. from Hainan province and Duplexissus gen. nov. with a new species D. punctatulus sp. nov. from Yunnan province. The photos of habitus and the male genitalia of the new species are provided. The biology, distribution and origin of the tribe Sarimini are discussed.